A Sharing Mind Map-oriented Approach to Enhance Collaborative Mobile Learning With Digital Archiving Systems - Chang, Jui-Hung; Chiu, Po-Sheng; Huang, Yueh-Min (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2018)
With the advances in mobile network technology, the use of portable devices and mobile networks for learning is not limited by time and space. Such use, in combination with appropriate learning strategies, can achieve a better effect. Despite the effectiveness of mobile learning, students’ learning direction, progress, and achievement may differ. Thus, the enhancement of learners’ opinions on the usability and interactivity during mobile learning are challenging issues to overcome. This study developed a sharing mind map-oriented mobile learning system integrated with valuable information preserved in a digital archiving system. In addition to the functions of traditional mind maps, this system also enabled students to complete and record relevant information that they had found onto the mind map and further improve the integrity of their own knowledge. To investigate the effectiveness of this teaching approach, this study added digital archive data and used mind map sharing to help learners develop knowledge.  By using the proposed approach, students were able to perform self-assessment on learning content, choose appropriate learning directions, and progress according to their level of learning. At the same time, they could collaboratively learn with peers to engage themselves more deeply in their learning. That is, their learning motivation could be constantly triggered through the observations and sharing of mind maps from one to another. This study selected sixth graders as its research subjects in two classes at the school where one researcher works. There were 31 and 30 valid samples in the experimental group and control group, respectively, with a total of 61 students. The experimental group was conducted by using sharing mind map with corresponding geographical archived information to investigate the effectiveness of sharing mind map (SMM) in mobile learning; on the other hand, the control group was conducted by using a traditional learning approach. The outcomes indicate that students’ learning performance could be enhanced by using archived information SMM mobile learning.